Facilitators and barriers to improved cookstove adoption: a community-based cross-sectional study in Northwest Ethiopia - Mesafint Molla Adane; Getu Degu Alene; Seid Tiku Mereta; Kristina Lutomya Wanyonyi (Komiyama Printing Co. Ltd, 2020)
Abstract Background Among the environmental risk factors, household air pollution exposure from traditional cooking practices is one of the biggest killers globally, which mainly impacts developing countries where many families rely on traditional cooking practices. Although improved cookstove adoption is central to tackle this public health issue, the efforts to disseminate cookstove technologies have faced challenges, and the adoption rates are reported to be very low in many developing countries including Ethiopia. Therefore, this study aimed to determine the magnitude and identify potential factors that may act as facilitators or barriers to adoption from users' point of view. Methods As part of the wider stove trial project, a cross-sectional study was conducted among a total of 5830 households under randomly selected clusters. The required data were collected through face-to-face interviews, and a backward stepwise logistic regression analysis technique was applied to evaluate the effect of potential predictor variables on adoption using adjusted odds ratio (AOR) as measures of effect. Results The prevalence of adoption was found to be 12.3% (95% CI 11.5-13.2), and households headed by females (AOR 1.96; 95% CI 1.24-3.10), private house ownership (AOR 4.58; 95% CI 3.89-6.19), separate cooking location (AOR 1.84; 95% CI 1.49-2.78), fuel purchasing (AOR 2.13; 95% CI 1.64-2.76), health benefit (AOR 1.76; 95% CI 1.15-2.70), optimistic social interaction (AOR 1.81; 95% CI 1.46-2.26), traditional suitability (AOR 1.58; 95% CI 1.28-1.95), stove use demonstration experience (AOR 2.47; 95% CI 1.98-3.07), cheap price (AOR 2.48; 95% CI 1.91-3.21), availability (AOR 1.81; 95% CI 1.5-1, 2.17), fuel-saving benefit (AOR 1.63; 95% CI 1.18-2.24), and more durable stove (AOR 1.71; 95% CI 1.30-2.26) of cookstove played a significant role as facilitators to adoption. In addition, lower educational level of head (AOR 0.31; 95% CI 0.23-0.42) and fuel processing requirement (AOR 0.55; 95% CI 0.44-0.70) of cookstove were found to be barriers for adoption. Conclusions Extremely lower improved cookstove adoption was observed due to household- and setting-related, cookstove technology-related, user knowledge- and perception-related, and financial- and market development-related factors. Therefore, to gain successful adoption, implementers and policymakers should consider those important factors in the implementation of clean cooking solutions to the community.